Hotel internet marketing channel, trust and purchase decision: 5 star hotel in Kuala Lumpur / Amril Mu’idzuddin Amrahi - Amrahi, Amril Mu’idzuddin (2013)
Internet has become a new way of communication where it generally used by most organizations. In most of the industry, internet is used as a marketing tool for them to promote their products and services. Including hotel industry, they also use internet as one of their promotion tools. Hotel internet marketing channel or online marketing channel is one of the ways for them to promote their products and services and now it is essential for most of the hotels in the world including Malaysia. All the products and services provided by the hotel usually been promote directly and indirectly by hotel internet marketing channels. The information provided and review from past experience in these channels is important because this is one of the factors to influence customer purchase decision. For the purpose of this study, the researcher tries to investigate the relationship between hotel internet marketing channels, trust and purchase decision of customer towards 5 star hotels in Kuala Lumpur. A quantitative approach was used in this paper where instrumentation design was based on the previous research. Questionnaire had been distributed to all 5 star hotels in Kuala Lumpur official Facebook fan page using online survey provider. From the findings, there is significant relationship between hotel internet marketing channels, trust and purchase decision. This study only focused on 5star hotels in Kuala Lumpur. This study provides a lot of knowledge about the hotel internet marketing channels. Moreover, this study can provides the practitioner knowledge about how the customer perceived when they get promotion from them through hotel direct and indirect marketing channels, which they can use to strategize their business. Nevertheless, this paper also provides with empirical findings on marketing practices for hotel manager.